2015
DOI: 10.1044/2015_jslhr-h-14-0272
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Partial Information Within and Across Modalities: Contributions to Spoken and Written Sentence Recognition

Abstract: Purpose: This study evaluated the extent to which partial spoken or written information facilitates sentence recognition under degraded unimodal and multimodal conditions. Method: Twenty young adults with typical hearing completed sentence recognition tasks in unimodal and multimodal conditions across 3 proportions of preservation. In the unimodal condition, performance was examined when only interrupted text or interrupted speech stimuli were available. In the multimodal condition, performance was examined wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…In the multimodal conditions, we examined how performance is affected by response timing. We compared the results to a recent study on analogous conditions with younger normal-hearing adults (Smith and Fogerty, 2015). These findings provide insight into how older listeners resolve partially degraded written and spoken information and how multimodal processing of these signals changes with age.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…In the multimodal conditions, we examined how performance is affected by response timing. We compared the results to a recent study on analogous conditions with younger normal-hearing adults (Smith and Fogerty, 2015). These findings provide insight into how older listeners resolve partially degraded written and spoken information and how multimodal processing of these signals changes with age.…”
Section: Introductionmentioning
confidence: 77%
“…Unimodal processing of partial speech and text information has been investigated in both younger and older normal-hearing listeners. Smith and Fogerty (2015) found, for younger normal-hearing adult listeners, significantly better sentence recognition for unimodal speech-only compared to text-only conditions across various proportions of signal preservation. While a direct comparison of speech versus text processing for older listeners has not been conducted to our knowledge, studies have compared performance between younger and older listeners, and revealed generally poorer performance by older listeners resolving partial speech and text information (e.g., Krull et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations